Analisis Hukuman Kebiri Kimia dan Pemasangan Alat Pendeteksi Elektronik Bagi Pelaku Kekerasan Seksual Terhadap Anak - Firmansyah, Muhammad; suphia, suphia; Nofitasari, Solehati (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2022)
Chemical castration and installation of electronic detectors are additional punishments for perpetrators of sexual crimes against children. The problem in this research is how the procedures and installation of electronic detection devices for perpetrators of sexual violence against children are based on Government Regulation number 70 of 2020 concerning Procedures for the Implementation of Chemical Castration, Installation of Electronic Detection Devices, rehabilitation, and Announcement of the Identity of the perpetrators of Sexual Violence against Children and what the impact that will be felt by perpetrators of sexual violence against children after receiving additional punishment in the form of chemical castration. The method used is a normative legal research method. The conclusion of this study is that the procedures for implementing chemical castration and the installation of electronic detection devices are in accordance with applicable government regulations and procedures, although there are still many bad impacts that will be experienced by perpetrators of sexual violence against children, on the other hand the government has implemented appropriate punishments and has thought about consequences and of course providing rehabilitation, all for the common good and efforts to reduce the level of sexual violence that occurs and is experienced by children.